Psicoeducación en padres de niños con trastornos del neurodesarrollo con estrés parental - Pizarro Vizcarra, Angela Mercedes (2022)
As the diagnoses of children with Neurodevelopmental Disorders (ND) have increased, it has led to the use of a more complex holistic approach, and this has shown high levels of stress in the primary caregivers of these children. The objective of this work was to carry out a review study with empirical research on the impact of psychoeducation on parental stress in parents of school-age children with Neurodevelopmental Disorders. The research search was carried out based on the PRISMA guide (Page et al., 2021), using the EBSCO, SCOPUS and PUBMED databases; selecting 10 studies with experimental and quasi-experimental designs. The results indicate that psychoeducation or parental training programs significantly reduce measures of parental stress, showing that those that have practical intervention guidelines have a slightly more significant impact than those of a theoretical nature, as well as programs that used techniques of mindfulness were the most effective. It was shown that psychoeducation not only has a positive influence on parental stress, but also on the general well-being of the family and the developmental progress of children with NT..